2011
DOI: 10.15560/11015
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians and reptiles of the Refúgio de Vida Silvestre Mata do Junco, municipality of Capela, state of Sergipe, northeastern Brazil

Abstract: The Brazilian Atlantic Rainforest has high diversity levels of amphibians and reptiles, but there is a lack of richness survey at several areas, while a high level of deforestation is already known. The biome is highly endangered in northeastern Brazil, and few protected areas have been the main mechanism for providing the habitat conservation. We studied the Refúgio da Vida Silvestre Mata do Junco, a recently established conservation unit in this biome, at the Capela municipality, in the state of Sergipe. Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…When handled, the individual flattened its body, performed erratic movements, produced cloacal discharge, and triangulated its head (N = 1) (Table 4). According to the literature, it is terrestrial and diurnal, and can be found within the leaf litter (Sawaya et al 2008;Morato et al 2011;Marques et al 2015), and does not seem to use disturbed areas (Sawaya et al 2008). Two specimens examined showed lizard fragments in their hindgut (MRCM 510,532).…”
Section: Rhachidelus Brazili Boulenger 1908mentioning
confidence: 99%
“…When handled, the individual flattened its body, performed erratic movements, produced cloacal discharge, and triangulated its head (N = 1) (Table 4). According to the literature, it is terrestrial and diurnal, and can be found within the leaf litter (Sawaya et al 2008;Morato et al 2011;Marques et al 2015), and does not seem to use disturbed areas (Sawaya et al 2008). Two specimens examined showed lizard fragments in their hindgut (MRCM 510,532).…”
Section: Rhachidelus Brazili Boulenger 1908mentioning
confidence: 99%
“…, with records from Alagoas State south to Bahia State; P. ramagii (Boulenger, 1888), distributed from Paraiba State to northern Bahia; and P. vinhai (Bokermann, 1975(Bokermann, "1974, with records only for southern Bahia State and eastern Sergipe State (Silvano and Pimenta, 2003;Juncá, 2006;Morato et al, 2011;Frost, 2014).…”
Section: Geographic Distribution Of Pristimantis Vinhaimentioning
confidence: 99%
“…A specimen was collected in the Mata do Buraquinho Permanent Preservation Area (7º08'42"S, 34º51'54"W) in the municipality of João Pessoa, Paraiba State (July 5, 2005), and seven additional specimens were collected in Mata do Açude Cafundó (07°10'S, 35°05'W) in the municipality of Cruz do Espirito Santo, located approximately 20 km west of the Mata do Buraquinho site (August 22, 2004 (Morato et al, 2011). It is probable that populations of P. vinhai will be found in forest fragments in Alagoas State (located between Sergipe and Pernambuco).…”
Section: Geographic Distribution Of Pristimantis Vinhaimentioning
confidence: 99%
“…The lizard Kentropyx calcarata Spix 1825 (Squamata, Teiidae) has a wide distribution in forested habitats in the Amazon and the Atlantic Forest (Avila-Pires, 1995), but it can also be associated with forest edge (Morato et al 2011) and disturbed areas (Prudente et al 2013). Hemidactylus mabouia (Moreau de Jonnès 1818) (Squamata, Gekkonidae) is an exotic species of lizard from Africa, without micro-environmental specificity that shows a close relationship with anthropic and perianthropic environments and occupies microhabitats, such buildings (Vrcibradic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hemidactylus mabouia (Moreau de Jonnès 1818) (Squamata, Gekkonidae) is an exotic species of lizard from Africa, without micro-environmental specificity that shows a close relationship with anthropic and perianthropic environments and occupies microhabitats, such buildings (Vrcibradic et al 2011). Tropidurus hispidus (Spix 1825) (Squamata, Tropiduridae) is found in open areas but it can also be associated with forest edge (Morato et al 2011) or be a generalist regarding to its habitat (Van Sluys et al 2004;Miranda et al 2012). This species is in constant contact with human inhabited areas (Vitt et al 2008).…”
Section: Introductionmentioning
confidence: 99%